The history of Bhutan - Phuntsho, Karma 1968- (Haus Publishing, 2013)
Karma Phuntsho's The History of Bhutan is the first book to offer a comprehensive history of Bhutan in English. Along with a detailed social and political analysis, it offers substantive discussions of Bhutan's geography and culture; the result is the clearest, richest account of this nation and its history ever published for general readers.